2020
DOI: 10.3390/foods9091226
|View full text |Cite
|
Sign up to set email alerts
|

The Use of a Nutrient Quality Score is Effective to Assess the Overall Nutritional Value of Three Brassica Microgreens

Abstract: Microgreens have immense potential for improving dietary patterns, but little information is available regarding their overall nutritional value. We evaluated the nutritional traits of three hydroponically grown Brassica microgreens by using a Nutrient Quality Score. Micro cauliflower, micro broccoli and micro broccoli raab were grown using nutrient solutions with three different NH4:NO3 molar ratios (5:95, 15:85, and 25:75). Protein, dietary fiber, β-carotene, α-tocopherol and mineral elements (Ca, K, Mg, Fe,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Estimated daily intake was determined using nutrient composition results from this study against a FDA reference amount customarily consumed (RACC) 31 . As in previous studies 31 , 50 , RACC was used for their mature forms i.e., leafy greens (85 g) since the RACC for microgreens is yet to be determined 51 .…”
Section: Methodsmentioning
confidence: 99%
“…Estimated daily intake was determined using nutrient composition results from this study against a FDA reference amount customarily consumed (RACC) 31 . As in previous studies 31 , 50 , RACC was used for their mature forms i.e., leafy greens (85 g) since the RACC for microgreens is yet to be determined 51 .…”
Section: Methodsmentioning
confidence: 99%
“…So far, studies on the health benefits associated with microgreens consumption have been mainly focused on their content in vitamins, carotenoids, phenols, and minerals, often in comparison with the edible components of their mature counterparts. , However, to the best of our knowledge, very limited attention has been paid to the exploration of lipids in microgreens, especially for those crops that are known to be a potential source of essential fatty acids. Indeed, only a study on the fatty acid content in the aerial part of microgreens of purslane (Portulaca oleracea L.), recently performed by Giménez et al, can be found in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 , 5 ]. Due to their low caloric value but high content of fiber and phytochemicals, these vegetables are particularly popular among people who want to follow healthy dietary patterns [ 6 ].…”
Section: Introductionmentioning
confidence: 99%